Optimization of limestone processing through detailed analysis - Vytiahanets, Valentyn; Pitak, Inna (CPN Publishing Group, 2024)
Analyzing limestone using nitrogen porosimetry is crucial for understanding its porous structure, which influences its physicochemical properties and suitability for various applications. Nitrogen porosimetry measures pore size distribution, specific surface area, and pore volume, which are essential for predicting limestone's behaviour in processes like heat treatment and carbonization. This study aimed to determine the surface area and pore size distribution of lime obtained from kiln firing. Using high-purity nitrogen, vacuum degassing, and adsorption-desorption methods, the study identified that the limestone sample exhibited both Type II and Type I isotherms, indicating the presence of nonporous/macroporous and microporous structures. The results revealed a heterogeneous pore structure with slotted and cylindrical pores, significantly impacting limestone's reactivity and water absorption properties. The findings suggest that nitrogen porosimetry is invaluable for optimizing limestone processing, ensuring product quality, and supporting sustainable material usage in construction. The study underscores the potential of using nitrogen porosimetry data to enhance the efficiency of limestone-based materials and processes.
Keywords: materials; sizes; limestone; optimization; water absorption